Development of resource distribution model of automated control system of special purpose in conditions of insufficiency of information on operational development - Shyshatskyi, Andrii; Sova, Oleg; Zhuravskyi, Yurii; Zhyvotovskyi, Ruslan; Lyashenko, Anna; Cherniak, Oleh; Zinchenko, Kateryna; Lazuta, Roman; Melnyk, Artur; Simonenko, Alexander (Technology audit and production reserves, 2019)
The paper considers the task of allocating the resources of an automated control system for special purposes in conditions of insufficient information on the development of the operational situation. The object of research is an automated control system for special purposes in the face of uncertainty in the operational environment and limited computing resources. One of the most problematic places in the distribution of resources of an automated control system is the low quality of planning, distribution and use of resources of an automated system in conditions of insufficient information about the operational situation and the inability to predict the actions of the enemy. This reduces the efficiency of both the system itself and its application. The scientific problem is solved with the help of developing a model for the distribution of system resources with the possible appearance of a lot of perturbations at the input, taking into account the features of the current operational situation in the course of the armed conflict and allows forecasting the state of the automated control system. In the course of the study, the authors of the work used the basic principles of queuing theory, automation theory, the theory of complex technical systems, as well as general scientific methods of cognition, namely analysis and synthesis. The novelty of the proposed model lies in the fact that it allows to justify the decomposition of the system. This allows to present a solution to the vector optimization problem in the binary relations of conflict, assistance and indifference. It also takes into account the operational environment and allows predicting the state of the system taking into account external influences, constructing utility functions and guaranteed payoff, as well as a numerical optimization scheme on this set. The proposed model will improve the efficiency of information processing due to its distribution and rational use of available computing resources. It is advisable to use the research results when planning the configuration of the data transmission system and at the stage of operational control of the resources of these systems.